The effects of ?-irradiation on some physical properties of Cu-13.5 wt.%Al-4 wt.%Ni shape memory alloy - Tatar, C; Zengin, R (Elsevier Science Bv, 2005)
The effects of gamma-irradiation on some physical properties of CuAlNi shape memory alloy were investigated. The hysteresis (A(p)-M-p) value for gamma-irradiated specimen was found as about 22.7 +/- 0.7 degrees C. The total oxidation for irradiated alloy rate was calculated. It was observed that the martensite morphology was distorted after gamma-irradiation. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Cu-Al-Ni alloy; irradiation; tansformation temperatures; oxidation behavior